Banking in the Shadow of Bitcoin? The Institutional Adoption of Cryptocurrencies - Raphael Auer; Marc Farag; Ulf Lewrick; Lovrenc Orazem; Markus Zoss (Center for Economic Studies and ifo Institute (CESifo), 2023)
The phenomenal growth of cryptocurrencies raises important questions about their footprint on the financial system. What role are traditional financial intermediaries playing in cryptocurrency markets and what drives their engagement? Are new nodes emerging? We help answer these questions by leveraging a novel global supervisory database of banks' cryptocurrency exposures and by synthesising a range of complementary data sources for other types of institutions. We find that major banks' exposures currently remain at very modest levels. Across countries, higher innovation capacity, more advanced economic development, and greater financial inclusion are associated with a higher likelihood of banks taking on cryptocurrency exposures. We show that substantial activity is concentrated in lightly regulated crypto exchanges. This "shadow crypto financial system" serves both retail and institutional clients, such as dedicated investment funds. An uneven regulatory treatment across banks and crypto exchanges and significant data gaps suggest that a proactive, holistic and forward-looking approach to regulating and overseeing cryptocurrency markets is needed. It should focus on ensuring a more level playing field with regard to financial services provided by established financial institutions and intermediaries in the emerging crypto shadow financial system by introducing more stringent regulatory and supervisory oversight for the latter.
Keywords: E42; G12; G21; G23; G28; O33; 330; cryptocurrencies; decentralised finance; digital currencies; financial regulation; financial supervision; exchange stablecoin; Bitcoin; Ethereum